Exosomal MiR-769-5p Exacerbates Ultraviolet-Induced Bystander Effect by Targeting TGFBR1 - Ni, Na; Ma, Weiwei; Tao, Yanling; Liu, Juan; Hua, Hui; Cheng, Jiawei; Wang, Jie; Zhou, Bingrong; Luo, Dan (Frontiers in Physiology, 2020)
Exosomal microRNAs have been investigated in bystander effect, but it is unclear whether microRNA works in ultraviolet radiation–induced bystander effects (UV-RIBEs) and what the underlying mechanism could be. Exosomes from ultraviolet (UV)–irradiated human skin fibroblasts (HSFs) were isolated and transferred to normal HSFs, followed by the detection of proliferation rate, oxidative damage level, and apoptosis rate. Exosomal miRNAs were evaluated and screened with miRNA sequencing and quantitative reverse transcriptase–polymerase chain reaction method. MiRNA shuttle and bystander photodamage reactions were observed after transfection of miR-769-5p. MiR-769-5p targeting gene transforming growth factor-β1 (TGFBR1), and TGFBR1 mRNA 3′-untranslated region (UTR) was assessed and identified by Western blotting and dual-luciferase reporter assay. Bystander effects were induced after being treated with isolated exosomes from UV-irradiated HSFs. Exosomal miR-769-5p expression was significantly upregulated. Human skin fibroblasts showed lower proliferation, increasing oxidative damage, and faster occurrence of apoptosis after transfection. Exosome-mediated transfer of miR-769-5p was observed. Upregulation of miR-769-5p induced bystander effects, whereas downregulation of miR-769-5p can suppress UV-RIBEs. In addition, miR-769-5p was found to downregulate TGFBR1 gene expression by directly targeting its 3′-UTR. Our results demonstrate that exosome-mediated miR-769-5p transfer could function as an intercellular messenger and exacerbate UV-RIBEs. MiR-769-5p inhibits the expression of TGFBR1 by targeting TGFBR1 mRNA 3′-UTR.